Newly trained operating room nurses’ experiences of nursing care in the operating room - Eriksson, Johan; Lindgren, Britt‐Marie; Lindahl, Elisabeth (Scandinavian journal of caring sciences, 2020)
There is limited research on nurses’ experiences of nursing care in the operating room. The operating room nurses’ responsibility is to ensure good nursing care before, during and after surgery. In an increasingly technological health care environment, there is always a risk of turning the focus away from nursing care towards technology and medicine. Integration of past experiences into the role as an operating room nurse becomes a challenge for those who recently worked as general nurses. The present study aimed to explore newly trained operating room nurses’ experiences of nursing care in an operating room. Semi‐structured interviews were performed with ten operating room nurses with a maximum three years’ work experience from an operating room. The interviews were subjected to qualitative content analysis. The findings revealed three themes describing operating room nurses’ searching for their new role. They experienced a gap between theory and practice, felt alone and insignificant and had to find their own place. The operating room nurses’ experienced threats to safe nursing when they lacked time for the patients as well as for their own recovery, and they lacked feedback in order to improve care. They ensured security for patients by establishing one‐to‐one contact, protecting patients’ well‐being and working in teams for the patients’ best interest, participants also focused on the task at hand instead of the patient as a person. New ways of organising work in operating units, and well‐functioning teams can be a key to a successful integration of experiences from ward nurse to an operating room nurse, and provide support so that they feel more visible, at ease and safe in their new profession.